2010
DOI: 10.1093/toxsci/kfq312
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Circuits Involved in the Middle-Ear Acoustic Reflex

Abstract: Human and animal studies have shown that certain aromatic solvents such as toluene can cause hearing loss and can exacerbate the effects of noise. The latter effects might be due to a modification of responses of motoneurons controlling the middle-ear acoustic reflex. In the present investigation, the audition of Long-Evans rats was evaluated by measuring cubic (2f1 - f2) distortion otoacoustic emissions (f1 = 8000 Hz; f2 = 9600 Hz; f1/f2 = 1.2) prior to, during, and after activation of the middle-ear acoustic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…This reflex is driven by a cholinergic efferent system. 76 This type of effect suggests that the hearing loss observed in solvent-exposed subjects might be due to dysfunctions beyond the peripheral auditory system, which could at least partially explain the synergistic effects of co-exposure to noise and aromatic solvents.…”
Section: Aromatic Solventsmentioning
confidence: 99%
See 2 more Smart Citations
“…This reflex is driven by a cholinergic efferent system. 76 This type of effect suggests that the hearing loss observed in solvent-exposed subjects might be due to dysfunctions beyond the peripheral auditory system, which could at least partially explain the synergistic effects of co-exposure to noise and aromatic solvents.…”
Section: Aromatic Solventsmentioning
confidence: 99%
“…76 A dysfunction of this reflex would increase risks to hearing by allowing higher acoustic energy levels to penetrate the inner ear. 75,82 This would make co-exposure more dangerous than exposure to noise or to styrene alone.…”
Section: Co-exposurementioning
confidence: 99%
See 1 more Smart Citation
“…In today's complex industrial environments, noise and chemicals, such as solvents, are found in many workplaces, and are part of the daily life of numerous workers. Studies conducted with experimental animals provide robust evidence that solvents, such as toluene, styrene, xylene, and ethyl benzene, can affect the auditory function through their toxic action on the organ of Corti, auditory pathways, as well as on the middle-ear reflex (Venet et al, 2011;Wathier et al, 2016). In addition, aromatic solvents can interact synergistically with noise.…”
mentioning
confidence: 99%
“…The mechanism behind this specific interaction involves an effect of solvents on acoustic reflexes. The middle-ear acoustic reflex (MER) is driven by a cholinergic efferent system and in vivo studies have shown that it can be affected by solvents (Maguin et al, 2009;Venet et al, 2011). A dysfunction of this reflex would increase the risk for hearing loss by allowing higher acoustic energy levels (at least 5 dB) to penetrate the inner ear (Campo et al, 2014;Carreres Pons et al, 2017).…”
mentioning
confidence: 99%